Analysis of the etiological characteristics of multidrug-resistant organisms and prognostic factors in ICU patients - Du, Fengxia; Ji, Qun; Li, Ying; Jia, Jing; Xi, Ruiping (Frontiers in Physiology, 2025)
BackgroundMultidrug-resistant organism (MDRO) infections contribute to high mortality in intensive care unit (ICU) patients, yet their specific pathogen profile and mortality risk factors are inadequately characterized.ObjectiveIn this study, we aim to investigate MDRO infections in ICU patients, identify prevalent pathogens, and evaluate risk factors associated with 28-day mortality.MethodsA retrospective study of 260 ICU patients with MDRO infections (resistant to ≥3 antimicrobial classes) analyzed the specimen types, infection sites, and pathogens. Patients were grouped (survival group and non-survival group) based on 28-day survival outcomes. Multivariate logistic regression identified prognostic factors, and the model’s validity, fit, and discriminatory power were assessed.ResultsIn ICU patients with MDRO infections, sputum was the most common test specimen, with the respiratory system as the main infection site. Pathogenic bacteria primarily included Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Staphylococcus aureus. Sixty-seven patients died within 28 days after enrollment (mortality rate: 25.77%). ICU length of stay [odds ratio (OR): 1.141; 95% confidence interval (CI): 1.020–1.275], Acute Physiology and Chronic Health Evaluation II (APACHE II) score upon admission (OR: 1.496; 95% CI: 1.261–1.775), comorbidity with cardiovascular and cerebrovascular diseases (OR: 4.620; 95% CI: 1.665–12.821), comorbidity with pulmonary diseases (OR: 4.150; 95% CI: 1.722–10.000), duration of mechanical ventilation >7 days (OR: 3.457; 95% CI: 1.502–7.955), and number of invasive procedures (OR: 1.845; 95% CI: 1.239–2.748) were independent risk factors for poor prognosis in ICU patients with MDRO infections. A logistic regression equation was developed: logistic regression equation = −20.646 + 0.132X1 (ICU stay) + 0.403X2 (APACHE II score) + 1.530X3 (cardiovascular/cerebrovascular comorbidities) + 1.423X4 (pulmonary comorbidities) + 1.240X5 (mechanical ventilation >7 days) + 0.613X6 (invasive procedures). The model was statistically significant (likelihood ratio chi-square test, P < 0.05) and demonstrated a good fit (Hosmer–Lemeshow test, P > 0.05). The area under the curve (AUC) was 0.913 (0.85 ≤ AUC <0.95), with 65.67% sensitivity, 93.78% specificity, and 86.54% accuracy in predicting the survival/death risk in MDRO-infected patients, indicating strong discriminatory power.ConclusionICU patients with MDRO infections exhibit diverse pathogens. Prompt preventive and control measures should be implemented based on the characteristics of MDRO infections and high-risk factors associated with prognosis to reduce the risk of death following MDRO infections.